Case Study of an Online Course on Introductory Mathematics for Artificial Intelligence (Research Journal of Mathematics & Technology, 2022)
Artificial Intelligence (AI) is one of the most crucial factor affecting future career choice of students.Accordingly, we offered students a semester-long Introductory Mathematics for Artificial Intelligencecourse. The course was developed to provide undergraduate students with various majors to navigatetheir career opportunities in AI-related jobs. This paper presents the newly published textbook and anonline mathematics laboratory that integrated effective technology for this introductory course. Inaddition, we introduce a process-driven evaluation method based on the Problem/Project-BasedLearning (PBL) report that worked well for this course. We also share trails of communications withour students and added the results of our students' performance analysis using principal componentanalyses (PCA) with the data generated from the class.